Cohort profile: Japanese human milk study, a prospective birth cohort: baseline data for lactating women, infants and human milk macronutrients - Kyoko Nomura; Keisuke Nojiri; Satoshi Higurashi; Tomoki Takahashi; Yuta Tsujimori; Shunjiro Kobayashi; Yasuhiro Toba; Jun-ichi Yamamura; Hiroshi M Ueno (BMJ Open)
Purpose The Japanese Human Milk Study, a longitudinal prospective cohort study, was set up to clarify how maternal health, nutritional status, lifestyle and sociodemographic and economic factors affect breastfeeding practices and human milk composition. This would eventually determine factors affecting the growth and development of infants and children.Participants A total of 1210 Japanese lactating women who satisfied the inclusion criteria, were invited across the country at various participating sites, between 2014 and 2019. Finally a total of 1122 women were enrolled in this study.Findings to date Among 1122 eligible participants, mean age at delivery was 31.2 (SD 4.4) years and mean prepregnancy BMI was 20.8 (SD 2.7). Among these women, 35% were previously nulliparous and 77.7% had college, university or higher education. The mean gestational period was 39.0 (SD 1.3) weeks. Caesarean section was reported among 11.9%; mean infant birth weight was 3082 (SD 360) g. Of the infants, 53.7% were male. Overall, our participants appeared to be healthier than the general population in Japan. Analyses of the 1079 eligible human milk samples obtained at the first and second months postpartum showed the following composition: carbohydrate, 8.13 (SD 0.32) g/100 mL; fat, 3.77 (SD 1.29) g/100 mL; and crude protein, 1.20 (SD 0.23) g/100 mL. We also analysed osteopontin, fatty acid, vitamin D and phospholipid levels in limited subcohorts of the samples.Future plans Follow-up surveys will be conducted to obtain milk samples every 2 months for 12 months and to investigate mother and child health until the children reach 5 years of age. These will be completed in 2024. We plan to longitudinally analyse the composition of macronutrients and various bioactive factors in human milk and investigate the lifestyle and environmental factors that influence breastfeeding practices, maternal and child health, and child development.Trial registration number UMIN000015494; pre-results.